Penguatan Ekonomi Melalui Inovasi Badan Usaha Milik Desa “Putra Mandiri” di Desa Selasari Kecamatan Parigi Kabupaten Pangandaran - Vani Mulyani; Kiki Endah; Teguh Anggoro (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Innovation is a research, development and engineering activity carried out with the aim of developing practical applications of new scientific values ​​and contexts or by applying existing science and technology in products or processes. Village-Owned Enterprises are institutions formed by the village government and the community manages these institutions based on the needs and economy of the village. The lack of optimal development of BUMDes business units causes quite large losses, partly due to the lack of cooperation carried out by the Village Government and BUMDes which then results in many tourist units being abandoned. ​This research is a descriptive study with a qualitative approach. The data in this research consists of primary data and secondary data. The informants in this research were 7 people, data collection techniques were through observation, interviews and documentation. Data management/data analysis techniques through data reduction, data presentation, drawing or drawing conclusions. ​In the interview results from the BUMDes Director, there was a decline in income, but not every year. The aim of this research is that it is hoped that BUMDes will have a big influence and be able to help develop the community's economy through the BUMDes business unit "Putra Mandiri" in Panggang Village so that it runs optimally. The results of the evaluation require training for BUMDes managers and their communities so that the development of BUMDes business units can run optimally.